Birthright. Volume four, Family history - Williamson, Joshua; Bressan, Andrei, 1978- (Zevin, Gabrielle., 2016)
The longer Mikey Rhodes remains on Earth, the more the evil within him is unleashed. As the remaining mages gather to take him down, a lost member of the Rhodes family returns ... but can they recover from the damage already done?